2009
DOI: 10.1152/ajpcell.00430.2008
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of monocarboxylate transporter 4 with β1-integrin and its role in cell migration

Abstract: Monocarboxylate transporter (MCT) 4 is a heteromeric proton-coupled lactate transporter that is noncovalently linked to the extracellular matrix metalloproteinase inducer CD147 and is typically expressed in glycolytic tissues. There is increasing evidence to suggest that ion transporters are part of macromolecular complexes involved in regulating beta(1)-integrin adhesion and cell movement. In the present study we examined whether MCTs play a role in cell migration through their interaction with beta(1)-integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 58 publications
5
58
0
1
Order By: Relevance
“…In this context, it is interesting that the Basigin/MCT4 complex has been found to associate with integrin β1 and localize at the leading edge of migrating cells, an area very active for invasive growth and also very demanding in metabolic energy (44). More importantly Philp et al (45) reported that silencing MCT4 but not MCT1 in retinal pigment epithelial cells slowed down their migration, a process highly controlled by pH.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is interesting that the Basigin/MCT4 complex has been found to associate with integrin β1 and localize at the leading edge of migrating cells, an area very active for invasive growth and also very demanding in metabolic energy (44). More importantly Philp et al (45) reported that silencing MCT4 but not MCT1 in retinal pigment epithelial cells slowed down their migration, a process highly controlled by pH.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, heterocomplexes of CD147 with MCT4 (primarily involved in monocarboxylate export) 4,5 have been previously reported to colocalize with b1-integrin at the leading edge lamellipodia of migrating cells, 45 supporting a role of MCTs in migration. Here, we documented that MCT1-CD147 complexes that accumulate in glucose-deprived cells are present among other locations in such protrusions ( Figure 5 and Supplementary Figure 5) and regulate the migratory phenotype ( Figure 6).…”
Section: Discussionmentioning
confidence: 85%
“…Additionally, silencing of MCT4 results in decreased cancer cell migration (Gallagher et al 2007), by mechanisms that also involve interaction of MCT4 with β 1 -integrin (Gallagher et al 2009). In opposition, another study showed that silencing of MCT1 or MCT4 inhibited cancer cell invasion, but did not influence cell migration (Izumi et al 2011).…”
Section: Mcts As Therapeutic Targets In Cancermentioning
confidence: 99%